Pandemics and emerging infectious diseases the sociological agenda - Dingwall, Robert; Hoffman, Lily M.; Staniland, Karen (2013)
The resurgence of infectious disease as a threat to public health in our globalized world presents social as well as biomedical challenges. This volume explores the sociological issues raised by pandemics that are as inevitable as they are unpredictable. How, for example, do we detect and identify new or resurgent diseases? How should public health authorities manage their responses? How does media coverage of pandemics affect public perceptions, and how can we generate awareness without panic? The contributors to this volume analyze case studies ranging from the scare over 'avian flu' that raised crucial questions of public interest, to the outbreak of H1N1 'swine flu' in 2009 and the West Nile virus, spread by a mosquito whose habitat is expanding in a warming world. Respected authors also tackle overarching issues of methodology and international governance, such as the imperative to coordinate supranational strategy in combating infections able to span the world as stowaways on passenger aircraft. Bringing together perspectives from North America, Europe and Asia, the book sets a bold sociological agenda informed by a keen awareness of the technical limitations of epidemiology, by newly forged links between public health and national security, and by geopolitical issues of development and social equity. It is a compelling intervention in an urgent policy debate. Book jacket.
"Originally published as Volume 35, Issue 2 of The Sociology of Health & Illness"--Title page verso.
Includes bibliographical references and index.
Keywords: Emerging infectious diseases -- Social aspects; Epidemiology; World health; Communicable Diseases, Emerging -- prevention & control; Epidemiology; Global Health; Electronic books